Requirements for Implementing E-tourism in Algeria - Bouriah , Selma; Keroui, Karima (Journal of Legal Studies and Researches, 2022)
This study deals with e-tourism as a modern form of tourism, resulting from the development of information and communication technologies, the growth and spread of which was made possible by globalization or so-called “globalized tourism”. This has contributed in increasing the number of tourists worldwide and in helping organize and develop the tourism sector in many countries. This study deals with the situation of e-tourism in Algeria it offers a realistic diagnosis of tourism and its related fields such as economy, e-commerce and the banking system, and suggests a number of measures that might help develop e-tourism in Algeria based on a productive, efficient, competitive and sustainable tourism sector.